ARE MANAGER POLICIES ASSOCIATED WITH EARNINGS MANAGEMENT ACTIVITY? - Rahmawati, Yuni; Prihatin, Bayu Triyo; Firmansyah, Amrie (Indonesian Journal of Accounting and Governance, 2023)
The effect of derivative ownership, leverage, and tax avoidance on earnings management isinvestigated in this study. From 2018 to 2021, samples were drawn from manufacturing sectorcompanies listed on the Indonesia Stock Exchange. Based on the purposive sampling technique, thisresearch sample included 72 observations. Multiple linear regression analysis was used to testhypotheses for panel data. The findings of the tests reveal that derivative ownership, leverage, and taxavoidance all have a detrimental impact on earnings management. Earnings management is not carriedout when a corporation has derivative instruments, excessive debt levels, and tax avoidance activities.This report advises that the Financial Services Authority monitor earnings management actions that aredamaging to shareholders' interests.